Reformatie: het verhaal van een ontologische leegte - Smalbrugge, Matthias (Tijdschrift voor theologie, 2017)
What is the Reformation about? Is it a reformation that really tries to offer an answer to the problems that late mediaeval theology had acutely laid bare? This is usually the approach taken when describing the Reformation. It is assumed to be a thorough revision of the basic assumptions of church doctrine, based on an elaboration of the doctrine of divine grace and wider soteriology. But is this impression correct? This is a relevant question as we commemorate 500 years of Reformation. If we want such a commemoration to be more than just looking back on history, we should also ask ourselves what the Reformation has meant for our current culture. What is the meaning of the Reformation in an era in which Europe is (again) in the grip of contradictions? Can the ideas and developments of 500 years ago help us find our bearings? Unfortunately, it seems that this is not the case. The Reformation, in particular in its earliest forms like with Luther, did not solve the problems of late mediaeval theology. It had adopted certain positions from that discourse and even made them more acute. This article will study this closer by looking at a number of developmental phases of the pre-reformatory process. First, it will consider the influence of Saint Augustine and his doctrine of grace, in particular his emphasis on predestination developed during the fight against Pelagianism. Second, it will look at the reception of Saint Augustine by non-theologian Petrarch. Petrarch appears to be looking for alternative ways because ratio and morals seem to have lost any foothold in Saint Augustine’s doctrine of grace. This is the first development of humanism, in which theology is still connected to culture, but appears to no longer contribute to it. Next, it looks at the developments in nominalism, which, with its emphasis on elements like contingency, free will and divine sovereignty, has burdened theology with some enormous problems. Luther does not solve these problems but instead contrasts the primacy of faith, Scripture and grace to the powerlessness of ratio and morals. At this point, the Reformation causes a split with culture, and from now on art, philosophy and literature will go their own way. Thus, the Reformation consolidated the crisis caused by nominalism and is still, because of its self-inflicted isolation, unable to offer any valuable orientations. This seems to suggest that it would be a better idea to start again from a pre-Reformation discourse like Petrarch’s and from nominalism.